2020
DOI: 10.1053/j.gastro.2019.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Post-Colonoscopy Colorectal Cancers Based on World Endoscopy Organization System of Analysis

Abstract: Causes of Post-colonoscopy Colorectal Cancers Based on WorldEndoscopy Organization System of Analysis BACKGROUND & AIMS: Postcolonoscopy colorectal cancer (PCCRC) is CRC diagnosed after a colonoscopy in which no cancer was found. A consensus article from the World Endoscopy Organization (WEO) proposed an approach for investigating and categorizing PCCRCs detected within 4 years of a colonoscopy. We aimed to identify cases of PCCRC and the factors that cause them, test the WEO system of categorization, quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 21 publications
7
99
2
2
Order By: Relevance
“…A recent analysis suggested that 89% of all PCCRCs may be avoidable, attributable to technical endoscopic factors, compromised decision-making, and administrative factors. 17 An adenoma detection rate (ADR) of 20% for individuals undergoing average-risk screening colonoscopy is a well-established quality indicator in CRC screening, first established in 2002 by the US Multi-Society Task Force on Colorectal Cancer. It is also known that ADR is inversely proportional to risk of developing PCCRC.…”
Section: Lessons Learned From Colorectal Cancer and Measurement Of Comentioning
confidence: 99%
“…A recent analysis suggested that 89% of all PCCRCs may be avoidable, attributable to technical endoscopic factors, compromised decision-making, and administrative factors. 17 An adenoma detection rate (ADR) of 20% for individuals undergoing average-risk screening colonoscopy is a well-established quality indicator in CRC screening, first established in 2002 by the US Multi-Society Task Force on Colorectal Cancer. It is also known that ADR is inversely proportional to risk of developing PCCRC.…”
Section: Lessons Learned From Colorectal Cancer and Measurement Of Comentioning
confidence: 99%
“…The miss rate dropped to~10% for all lesions measuring ≄10 mm, but it remained high (~25%) for the lesions that were sessile or flat, the subset that includes SSLs. Most CRCs detected within 3 years of a negative colonoscopy derive from missed or incompletely-excised lesions, and these "interval" or "post-colonoscopy" malignancies are characterized by an over-representation of proximal-colon locations and cancers that develop along the serrated tumorigenic pathway [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The miss rate dropped to ~ 10% for all lesions measuring ≄10 mm, but it remained high (~ 25%) for the lesions that were sessile or at, the subset that includes SSA/Ps. Most CRCs detected within 3 years of a negative colonoscopy derive from missed or incompletely-excised lesions, and these "interval" or "post-colonoscopy" malignancies are characterized by an overrepresentation of proximal-colon locations and cancers that develop along the serrated tumorigenic pathway [23] [24][25] [26].…”
Section: Introductionmentioning
confidence: 99%